Safety and Efficacy of Indomethacin for Reducing Chest Tube Duration After Coronary Artery Bypass Grafting Surgery. (June 2022) - Gibson, Caitlin M.; Hall, Brenton; Kwon, Hyanggi Irene; Davis, Sondra; Bradford, Darien; Howard, Meredith L.
Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) contain a boxed warning for use in coronary artery bypass graft (CABG) surgery due to increased risk of thrombotic events, but recent research has challenged the assumption that these risks are a class effect. One anecdotal indication for NSAIDs in CABG is reducing chest tube output.Objective: The primary objective of this retrospective study was to determine whether indomethacin was associated with reduced duration of chest tube insertion after CABG surgery, defined as total chest tube duration in controls versus duration of chest tube insertion after the first dose of indomethacin in the treatment group. Secondary objectives were comparisons of daily reductions in chest tube output volume, length of stay, and safety between groups.Methods: In this retrospective, single-center case-control review, adult patients who received indomethacin after CABG were matched 1:1 to control patients based on age, sex, concomitant valve surgery, and, when possible, diabetes status.Results: Thirty-two patients were included. The mean age was 56 years and 75% were men. The primary outcome measure was 94 hours among control patients and 82.8 hours among indomethacin patients ( P = 0.041). Insignificant mean reductions in daily chest tube output were observed prior to and after indomethacin initiation (38.7 vs 87.7 mL/day, P > 0.05).Conclusion: In this small, single-center study, indomethacin appeared safe and possibly effective for reducing chest tube duration after CABG surgery. Future large, prospective, randomized studies should be conducted to confirm the results.